(untitled) (Academicia Globe: Inderscience Research, 2022)
Nowadays, in many developed countries, the digital economy and the factors of their development have a significant impact, and the digital economy plays an important role in the life of society. In this article, you can find answers to questions such as "What is the digital economy?", "Tasks and goals of the digital economy", "Obstacles in the development of the digital economy in Uzbekistan" about the digital economy.